Follow-up observations for IceCube-170922A: Detection of rapid near-infrared variability and intensive monitoring of TXS 0506+056. (22nd January 2021) - Morokuma, Tomoki; Utsumi, Yousuke; Ohta, Kouji; Yamanaka, Masayuki; Kawabata, Koji S; Inoue, Yoshiyuki; Tanaka, Masaomi; Yoshida, Michitoshi; Itoh, Ryosuke; Sasada, Mahito; Tominaga, Nozomu; Mori, Hiroki; et al.
Abstract: We present our follow-up observations to search for an electromagnetic counterpart of the IceCube high-energy neutrino IceCube-170922A. Monitoring observations of a likely counterpart, TXS 0506+056, are also described. First, we quickly took optical and near-infrared images of seven flat-spectrum radio sources within the IceCube error region right after the neutrino detection and found a rapid flux decline of TXS 0506+056 in Kanata/HONIR J -band data. Motivated by this discovery, intensive follow-up observations of TXS 0506+056 were continuously performed, including our monitoring imaging observations, spectroscopic observations, and polarimetric observations in optical and near-infrared wavelengths. TXS 0506+056 showed a large-amplitude (∼1.0 mag) variability in a time scale of several days or longer, although no significant variability was detected in a time scale of a day or shorter. TXS 0506+056 also showed a bluer-when-brighter trend in optical and near-infrared wavelengths. Structure functions of the variabilities were examined and indicate that TXS 0506+056 is not a special blazar in terms of optical variability. Polarization measurement results of TXS 0506+056 are also discussed.